Reduced Cognitive Processing of Alcohol Cues in Alcohol-Dependent Patients Seeking Treatment: An ERP Study. Issue 3 (July 2013) - Littel, Marianne; Field, Matt; van de Wetering, Ben J. M.; Franken, Ingmar H. A.
Substance-dependent individuals have been shown to display increased P3 amplitudes in response to substance-related stimuli. The P3 component of the event-related potential (ERP) has been associated with 'motivated attention' for substance cues. Enhanced processing of substance cues has not been unequivocally demonstrated in alcohol-dependent patients. The main goal of the present study was to further investigate electrophysiological processing of alcohol and non-alcohol (soft drink) cues in alcohol-dependent patients and controls. In addition, it was examined whether groups differed in the processing of positive emotional cues. Results showed that alcohol-dependent patients did not respond with more enlarged P3 amplitudes to alcohol cues than soft drink cues. At fronto-central sites they even showed reduced alcohol cue-elicited P3 amplitudes as compared to controls. These results are in line with results from studies using behavioral measures of cognitive processing and might be explained by the use of avoidance strategies, i.e., patients' effort to remain abstinent or control their alcohol use. There were no differences between groups regarding the processing of positive cues. Interpretations and implications of the findings are discussed.